If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4v + -6)(1 + v) = 0 Reorder the terms: (-6 + 4v)(1 + v) = 0 Multiply (-6 + 4v) * (1 + v) (-6(1 + v) + 4v * (1 + v)) = 0 ((1 * -6 + v * -6) + 4v * (1 + v)) = 0 ((-6 + -6v) + 4v * (1 + v)) = 0 (-6 + -6v + (1 * 4v + v * 4v)) = 0 (-6 + -6v + (4v + 4v2)) = 0 Combine like terms: -6v + 4v = -2v (-6 + -2v + 4v2) = 0 Solving -6 + -2v + 4v2 = 0 Solving for variable 'v'. Factor out the Greatest Common Factor (GCF), '2'. 2(-3 + -1v + 2v2) = 0 Factor a trinomial. 2((-1 + -1v)(3 + -2v)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-1 + -1v)' equal to zero and attempt to solve: Simplifying -1 + -1v = 0 Solving -1 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1v = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1v = 0 + 1 -1v = 0 + 1 Combine like terms: 0 + 1 = 1 -1v = 1 Divide each side by '-1'. v = -1 Simplifying v = -1Subproblem 2
Set the factor '(3 + -2v)' equal to zero and attempt to solve: Simplifying 3 + -2v = 0 Solving 3 + -2v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2v = 0 + -3 -2v = 0 + -3 Combine like terms: 0 + -3 = -3 -2v = -3 Divide each side by '-2'. v = 1.5 Simplifying v = 1.5Solution
v = {-1, 1.5}
| 99.08/100*40.65=x | | 8n=6-14 | | 5x-2-7x=4+x-1 | | -2x-1/16=-6x^2 | | 56=4h/7 | | X^4-12x^4+48x^2-64=0 | | -7w=-91 | | -22=-p | | 8t-20=6t+10 | | 15n^2+19n+6=10+2n | | 3x^2+10x+15=-4X | | 15n^2+19+6=10+2n | | 0.02*40.65=x | | (x-2)=36 | | -64+30m=-34 | | 40.65*x=1 | | 18w+25=205 | | x+0.25x=1 | | X^2+36y^2-16x-72y+64=0 | | 32-4x=4 | | 8k=3k+75 | | 8m^2+2m+4=7 | | 8m^2+2m-3=7 | | -t=85 | | 15y-6y=22 | | t^2/2+2t=1/4 | | 4z^2+9z/z | | -12+10-10= | | 2b+5=115 | | 17w-16=17+16w | | 216p^6-125q^3=0 | | (t^2)/2+2t=1/4 |